Pelatihan Penyusunan Modul Ajar Matematika Berorientasi Kemampuan Berpikir Kritis bagi Guru Matematika SMK Kota Mataram - Baidowi Baidowi; Sri Subarinah; Laila Hayati; Dwi Novitasari; Ni Made Intan Kertiyani (Rengganis Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service activity aims to provide training and assistance to SMK teachers in Mataram City to compile and develop mathematics teaching modules, especially by implementing project-based learning and problem-based learning. Participants in this community service activity consisted of teachers at 8 State Vocational Schools in Mataram City, which are represented by 2 teachers in each partner school. These activities carried out are (1) Dissemination of research results on the development of mathematics teaching modules that have been developed by the team, (2) Training on how to compile mathematics teaching modules oriented to students' critical thinking skills, (3) Discussion, (4) Practice compiling teaching modules in groups and (5) Evaluation of the implementation of activities. At the end of the activity, a questionnaire was given to be filled in by the participants and then analyzed to find out the results of the service activities provided. The results of data analysis showed that all participants gave a positive response, 67% of participants had received training in module preparation, 73% had made mathematics teaching materials but only 27% had implemented them, especially those oriented to critical thinking skills. Analysis of the questionnaire also showed that all participants wanted similar training. One of the trainee teachers successfully implemented the teaching module they had developed by the team from the results of the training and gave a positive response from the students